ANALYSIS OF METAL CONTENT OF Pb, Cr, Cu, AND Zn IN GONGGONG SNAIL (Strombus canarium) FROM COASTAL WATERS OF SINGKEP ISLAND LINGGA REGENCY OF RIAU ARCHIPELAGO PROVINCE - Meiji Nurdiansyah; Bintal Amin; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted in December 2017 in the coastal waters of Singkep Island, Lingga Regency, Riau ArchipelagoProvince. The purpose of this research was to analyse the content of metal Pb, Cr, Cu and Zn on soft tissue in gonggong snail (S. canarium) with different size and from two different stations. This study also determine the status of heavy metal pollution based on MPI (Metal Pollution Index) value and the feasibility consumption of gonggong snail. Analysis of metal content of heavy metal based on Yap et al., (2003). The results showed that the highest metal content of Pb was found in large snail size (1.1827 µg/g) at Station 2 and the highest Cr content was found in medium-sized snails (1.4053 µg/g) at Station 2. Highest Cu (27.9133 µg/g) in Station 1 and the highest Zn content was foundin large snail size (52.3273 µg/g) at Station 1. Average Cu and Zn content (23.7581 µg/g and 48.2146 µg/g) was higher than that of Pb and Cr (0.7800 µg/g and 1.0089 µg/g) in snails soft tissues. The MPI value of Singkep Island waters was 5.48 which was still relatively low. Based on the calculation of PTWI, gonggong snail in Singkep Island waters was still safe and feasible to be consumed for not exceeding the safe limits of consumption that has been determined, these are for Pb (8.9755 kg/week), Cr (6.3832 kg/week), Cu (41.2491 kg/week), and Zn (40.6516 kg / week). Key Words: Singkep Island, Heavy Metal, Pollution, Gonggong Snail (Strombus canarium)